A Novel Mechanism for Protein Delivery by the Type 3 Secretion System for Extracellularly Secreted Proteins - Farid Tejeda-Dominguez (mBio, 2017)
The type 3 secretion system (T3SS) is essential for bacterial virulence through delivering effector proteins directly into the host cytosol. Here, we identified an alternative delivery mechanism of virulence factors mediated by the T3SS, which consists of the association of extracellularly secreted proteins from bacteria with the T3SS to gain access to the host cytosol. Both EspC, a protein secreted as an enteropathogenic Escherichia coli (EPEC) autotransporter, and YopH, a protein detected on the surface of Yersinia, require a functional T3SS for host cell internalization; here we provide biophysical and molecular evidence to support the concept of the EspC translocation mechanism, which requires (i) an interaction between EspA and an EspC middle segment, (ii) an EspC translocation motif (21 residues that are shared with the YopH translocation motif), (iii) increases in the association and dissociation rates of EspC mediated by EspA interacting with EspD, and (iv) an interaction of EspC with the EspD/EspB translocon pore. Interestingly, this novel mechanism does not exclude the injection model (i.e., EspF) operating through the T3SS conduit; therefore, T3SS can be functioning as an internal conduit or as an external railway, which can be used to reach the translocator pore, and this mechanism appears to be conserved among different T3SS-dependent pathogens.